Postcoital Haemoptysis: A Case Report and a Review of the Literature - Emeka B. Kesieme; Browne C. Okonkwo; Peter O. Okokhere; Georgi Prisadov; Eghosa Aigbe; Christopher Affusim (Case Reports in Medicine)
Haemoptysis is rarely reported following coitus, and cardiac decompensation has been mostly implicated in the aetiology. We present a 53-year-old Nigerian, known hypertensive diabetic woman with background ischaemic heart disease who presented with postcoital haemoptysis of one-year duration. Echocardiography revealed combined ischaemic and mitral valvular heart disease, probably of rheumatic aetiology. There has been no previous report in an African population. This case illustrates the need to rule out coitus as a rare but potential cause of haemoptysis in middle aged patients with underlying cardiac pathologies and the need for an extensive cardiac workup in a population with predominantly pulmonary causes of haemoptysis.